COMMUNICATIVE LANGUAGE TEACHING IN ACADEMIC LYCEUMS - UMAROVA VAZIRA KHOLMURAD QIZI (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article examines the implementation of Communicative Language Teaching (CLT) in academic lyceums. CLT focuses on developing students’ communicative competence by encouraging real-life interaction and meaningful language use. The paper discusses the principles of CLT, its advantages, and practical techniques for classroom application. Special attention is given to the role of the teacher, student engagement, and the challenges faced in academic lyceums. The article highlights how CLT can improve students’ speaking, listening, and overall language proficiency.